2004
DOI: 10.1007/s11663-004-0054-0
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of thin-slab casting by the compact-strip process: Part I. Heat extraction and solidification

Abstract: This article reports on an extensive experimental and modeling study undertaken to elucidate the thermal evolution of thin slabs during their passage through the mold and secondary cooling system of a compact-strip process (CSP) caster. In industrial trials covering a wide range of casting conditions, temperature measurements were carried out at (1) the copper plates of an operating mold and (2) the stainless steel frame of an operating grid. Separately, water-flux and heat-flux distributions generated by the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
54
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 44 publications
(59 citation statements)
references
References 10 publications
5
54
0
Order By: Relevance
“…[37,38] Thus, in the present study, it is conjectured that observation of the motion of a slag surface, devitrifying at those temperatures, in relation to a stationary surface parallel to it would shed light on the formation of the gap-due to shrinkage-that has been claimed so profusely in the literature. To carry out these observations, glass samples in the form of parallelepipeds 2 9 6 9 4 mm 3 (thickness 9 width 9 height) are prepared.…”
Section: Observation Of Simulated Mold Flux Interfacementioning
confidence: 68%
See 4 more Smart Citations
“…[37,38] Thus, in the present study, it is conjectured that observation of the motion of a slag surface, devitrifying at those temperatures, in relation to a stationary surface parallel to it would shed light on the formation of the gap-due to shrinkage-that has been claimed so profusely in the literature. To carry out these observations, glass samples in the form of parallelepipeds 2 9 6 9 4 mm 3 (thickness 9 width 9 height) are prepared.…”
Section: Observation Of Simulated Mold Flux Interfacementioning
confidence: 68%
“…To compare the total effective thermal resistance, R T , determined in the laboratory with values estimated from industrial trials involving CSP molds, computational calculations reported by the authors [37] are used. The mold studied is straight in the casting direction and has a funnel-shaped section across its central upper part.…”
Section: Analysis Of Plant Datamentioning
confidence: 99%
See 3 more Smart Citations